Belajar Bahasa dan Sastra itu Seru (BeBaSaRu): An Early Childhood Literacy Development Program - Etty Umamy; Kustyarini Kustyarini; Dewi Anta Sari; Aisa Sri Rejeki; Mochamad Irwan Almustofa (Komunitas Dosen Indonesia, 2025)
Early literacy is a fundamental foundation in the cognitive and language development of young children. However, many children still face difficulties in recognizing letters, understanding vocabulary, and constructing simple sentences. The Belajar Bahasa dan Sastra itu Seru (BeBaSaRu) program was designed as a community engagement initiative to enhance early literacy skills through an interactive and engaging approach. This program aims to develop young children's reading, writing, and storytelling abilities while also strengthening the role of teachers and parents in literacy stimulation. The methods used in this program include a participatory approach that involves teacher training, parental education, and the implementation of phonemic games, storytelling, shared reading, and creative writing activities. The results indicate that the program effectively improved children's vocabulary, story comprehension, storytelling skills, and basic writing abilities. Moreover, it increased children's interest in reading and reinforced the active involvement of teachers and parents in supporting literacy development. The implications of this study suggest that interactive literacy teaching methods can be adapted to various educational settings, including schools with limited resources. The sustainability of this program requires support from multiple stakeholders to ensure that its approaches continue to be effectively implemented in early childhood literacy education.